Guide to wild foods and useful plants - Nyerges, Christopher (Chicago Review Press, 2014)
"An array of abundant wild foods is available to hikers, campers, foragers, or anyone interested in living closer to the earth. Written by a leading expert on wild foods and a well-known teacher of survival skills, Guide to Wild Foods and Useful Plants is more than a listing of plant types--it teaches how to recognize edible plants and where to find them, their medicinal and nutritional properties, and their growing cycles. This new edition features more than 70 plants found all around the United States along with more than 100 full-color photos plus a handy leaf key to help readers identify the plants. It also includes fascinating folklore about plants, personal anecdotes about trips and meals, and simple and tasty recipes"--Publisher's description